Performance characteristics and energy-exergy analysis of solar-assisted heat pump system - Dikici, Aydin; Akbulut, Abdullah (Pergamon-Elsevier Science Ltd, 2008)
In this study solar-assisted heat pump (SAHP) system with flat plate collectors was investigated experimentally and tested for domestic space heating. SAHP system was located in a test room with 60 m(2) floor area in Firat University, Elazig (38,41 degrees N, 39,14 degrees E) Turkey. The experiments were performed in heating season of January 2003. The coefficient of performance of the SAHP system was calculated. The system COP of the SAHP was obtained as 3.08 while the exergy loss of the solar collector wits found to be 1.92 kW. The second law efficiency of the compressor, condenser, evaporator and solar heat exchanger in SAHP system were evaluated 42.1%, 83.7%, 43.2% and 9.4%, respectively. The first law efficiency and exergetic efficiency of the whole system are found to be 65.6%, 30.8%, respectively. Consequently the energy and exergy loss analysis results show that the COP increase when the exergy loss of evaporator decrease. (C) 2007 Published by Elsevier Ltd.
Keywords: solar-assisted heat pump; energy analysis; exergy analysis; coefficient of performance